Sleep Architecture in Night Shift Workers Police Officers with Obstructive Sleep Apnea-hypopnea Syndrome - Verde-Tinoco, Selene; Santana-Miranda, Rafael; Gutiérrez-Escobar, Romel; Haro, Reyes; Miranda-Ortiz, Joana; Berruga-Fernandez, Talia; Jimenez-Correa, Ulises; Poblano, Adrián (Sleep Science, 2017)
Introduction Reduced sleep to increase work hours is common among police officers, when this situation is combined with Obstructive sleep apnea/hypopnea syndrome (OSAHS), health consequences are greater, therefore we believe there is a need of research for these alterations. The aim of this study was to measure the changes in sleep architecture (SA) in police officers who currently have Night shift work (NSW) and OSAHS.METHODS We compared SA in 107 subjects divided in three groups: the first group included police officers with NSW and severe OSAHS (n = 48); the second group were non-police officers with diurnal work time and severe OSAHS (n = 48) and the third group was formed by healthy controls (n = 11). Polysomnography (PSG) variables and Epworth sleepiness scale (ESS) scores were compared.Results SA was more disrupted in the group of police officers with NSW and OSAHS than in patients with OSAHS only and in the control group. Police officers with NSW and OSAHS presented an increased number of electroencephalographic activations, apnea/hypopnea index, and sleep latency, and showed lower scores of oxygen saturation, and in the ESS. Multivariate analysis revealed significant influence of age and Body mass index (BMI).Conclusions Data suggested with caution an additive detrimental effect of NSW and OSAHS in SA and ESS of police officers. However age and BMI must be also taken into account in future studies.
Keywords: Sleep Apnea Syndromes; Polysomnography; Night Work